Morphology and fractal dimension of TiO2 thin films - Srdjan P Petrović (Macedonian Journal of Chemistry and Chemical Engineering, 2013)
The influence of annealing temperature on the morphology and surface fractal dimension of titanium dioxide (TiO2) films prepared via the spray deposition process was investigated. Thin films with various morphologies were obtained at different temperatures and characterized by X-ray diffraction and atomic force microscopy (AFM). It was found that the crystalline structure of TiO2 films depends strongly on annealing temperature. At higher temperatures, the partial phase transformation of anatase-to-rutile was observed. The morphology and surface fractal dimensions were evaluated by image analysis methods based on AFM micrographs. The results indicate that the value of surface roughness (the standard deviation of the height values within the given area of AFM image) of TiO2 films increases with increasing annealing temperature. Fractal analysis revealed that the value of the fractal dimension of the samples decreases slowly from 2.23 to 2.15 following the annealing process.